Dual-functional photocatalysis using a ternary hybrid of TiO2 modified with graphene oxide along with Pt and fluoride for H-2-producing water treatment - Cho, Young-Jin; Kim, Hyoung-il; Lee, Seockheon; Choi, Wonyong (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2015)
Dual-functional photocatalysis for simultaneous H-2 production and degradation of organic pollutants has been proposed as an ecofriendly method of water treatment. In this study, we designed and prepared TiO2 modified with ternary components (graphene oxide (GO), Pt, or fluoride (or phosphate)) to enhance the dual-functional photocatalytic activity. The photocatalytic and photoelectrochemical properties of the ternary hybrid photocatalyst were investigated and compared with those of photocatalysts modified with binary components (Pt/TiO2-F, GO/TiO2-F, and Pt/GO/TiO2). Pt/GO/TiO2-F showed 1.7 and 3.8 times higher H-2 production than Pt/TiO2-F and Pt/GO/TiO2, respectively. GO layers on TiO2 appeared to attract electrons, and interfacial electron transfer was facilitated by direct contact between GO and the TiO2 surface. However, the positive effect of GO on the dual photocatalytic activity was observed only when Pt and surface fluoride were co-present. The presence of GO facilitates electron transfer to Pt, while the presence of surface fluoride that substitutes for the surface hydroxyl groups (hole trap site) reduces the number of surface trapped holes and subsequently retards surface recombination. The dual-functional photocatalytic activity of Pt/GO/TiO2 F was maintained during repeated photocatalysis runs using the same batch of catalyst. The positive effect of GO on ternary hybrid titania was also observed when phosphate was used instead of fluoride. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: HETEROGENEOUS PHOTOCATALYSIS; HYDROGEN GENERATION; NOBLE-METAL; DEGRADATION; NANOCOMPOSITES; NANOPARTICLES; SURFACE; FLUORINATION; ADSORPTION; POLLUTANTS